DIGITAL MARKETING AND INSTITUTIONAL SUPPORT AS DRIVERS OF REGIONAL SMALL BUSINESS DEVELOPMENT - KRAVCHYK, Yurii; MOSKALYUK, Oleksandr; SOLOMKO, Denis (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the context of the digital transformation of the economy, the development of small businesses significantly depends on the ability to adapt modern marketing tools, in particular digital marketing, to increase competitiveness, expand the customer base and optimize the costs of promoting goods and services. At the same time, small businesses, especially in the regions, often face barriers — from a lack of financial resources to limited access to digital technologies. This necessitates effective institutional support from state and local authorities, business associations, entrepreneurship development centers, etc. Such institutions should play a key role in creating an enabling environment for the digitalization of small businesses, providing advice, educational services, financial assistance, and infrastructure support. Today, the study of the relationship between institutional support and the implementation of digital marketing in regional small businesses is extremely relevant. It allows us to identify effective approaches to strengthening the role of small business in the sustainable development of regions, as well as to form recommendations for improving the effectiveness of small business support programs in the digital economy. Despite the rapid development of digital technologies and the growing availability of digital marketing tools, a significant part of small businesses in the regions of Ukraine remains on the periphery of these transformations. Entrepreneurs often do not have enough awareness, technical knowledge, or financial resources to effectively implement digital promotion strategies. At the same time, institutional support from state and local authorities, business associations and donor organizations, although declared, is not always systematic, targeted and adapted to the real needs of small businesses in specific regions. Lack of proper coordination between support entities, fragmentation of programs and weak analytical base limit the effectiveness of the digital transformation of small businesses. The purpose of this study is to comprehensively study the role of digital marketing and institutional support in stimulating the development of small businesses in the regions, as well as to identify effective mechanisms for their interaction to increase the competitiveness and sustainable economic growth of small businesses in the context of digital transformation. In today’s world, digital technologies are dynamically transforming the economic environment, changing the rules of doing business, ways of communicating with customers, and means of popularizing products and services. In this vein, digital marketing becomes crucial for ensuring the viability and competitiveness of small businesses, especially in regions where entrepreneurial activity is often limited by resources, infrastructure, and access to modern knowledge. Small business is the basis of the economy of most countries, because it provides market flexibility, promotes employment of the population, and stimulates the development of local communities. However, in many regions, these enterprises remain vulnerable to economic changes, without adequate access to digital transformation technologies. They face a number of barriers — from the lack of the necessary technical base to a lack of qualified personnel and knowledge in the field of digital marketing In today’s digital transformation environment, the effective use of digital marketing is one of the important factors for the long-term growth of small businesses, especially on a regional scale. The use of digital technologies creates additional ways to effectively promote goods and services, improve communication with customers, analyze the market situation and optimize costs. At the same time, the success of their application depends not only on the technological base of the enterprise, but also on the level of digital competence of the staff, strategic vision and flexibility of management decisions. At the same time, institutional support for small businesses plays an important role — through educational programs, consulting services, tax incentives, access to digital infrastructure and platforms. Coordination of efforts of government agencies, business associations, incubators and local initiatives contributes to the formation of a favorable environment for the implementation of innovative marketing strategies.